Speciální typy ložisek a jejich aplikace - Polášek, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Cílem této bakalářské práce je poskytnout rešeršní rozbor speciálních typů ložisek. Práce je zaměřena především na magnetická a vzduchová ložiska, která jsou z kategorie speciálních ložisek nejvíce dostupné a využívané. Oba tyto druhy jsou bezkontaktní ložiska, z čehož vyplývá velká část jejich výhod. V práci jsou uvedeny nejčastější typy konstrukčních řešení magnetických i vzduchových ložisek a vysvětleny principy funkce těchto ložisek. Na závěr jsou sepsány výhody použití a shrnuty možnosti aplikací těchto ložisek.

The goal of this bachelor’s thesis is to provide a search analysis of special bearing types. This work is focused especially to magnetic and air bearings, which are the most available and used special bearings. Both of these types are contactless, from which follows a big part their benefits. In this thesis there are introduced and explained the principles and design solutions of the most frequently used types of magnetic and air bearings. At the conclusion there are written up advantages and possible uses of these bearings.
Special bearing types and its application
Keywords: speciální typy ložisek; magnetické ložiska; magnetická levitace; vzduchová ložiska; special types of bearing; magnetic bearings; magnetic levitation; air bearings